An abattoir-based study on the prevalence of hydatidosis infestation and fertility of hydatid cysts in slaughtered herbivores (food animals) in Dhamar Province-Yemen - Ahmed Odhah, Mohammed Naji; Almashhadany, Dhary Alewy; Otaifah, Abdullah Garallah; Garba, Bashiru; Mohammed Salah, Najeeb; Abdullah Jesse, Faez Firdaus; G.K, Mohd Azam Khan (Nexus Academic, 2022)
Cystic echinococcosis is one of the most important emerging zoonotic parasitic diseases worldwide. This disease causes considerable economic losses and adverse public health challenges in most countries, including the Middle East countries. This study was designed to investigate the current prevalence of hydatidosis and to determine the fertility of hydatid cysts among some ruminants (both local and imported breeds of cattle, sheep, and goats) slaughtered in the abattoirs in Dhamar Province-Yemen. The samples were collected from the Central Corporation Slaughterhouse in Dhamar-Yemen from January 2019 to November 2020. During this period, a total of 29,071 and 5,705 samples were collected from local and imported food animals respectively. The results of analysed samples revealed that the distribution of the hydatid cysts among the local slaughtered animals were 318 (11 .63%), 613 (5.41%), and 28 (6.08%) for cattle, sheep, and goats respectively for the year of 2019 whereas in the year 2020, the results were 235 (9.69%), 685 (5.74%) and 32 (6.95%) respectively. Moreover, the prevalence rates of hydatidosis among the imported animals in the year 2019 (cattle, sheep, and goats) were 71 (4.76%), 36 (3.0%) and 39 (5.93%) while 93 (5.28%), 24 (4.8%) and 34 (6.8%) were recorded in the year 2020, respectively. With respect to the fertility rates of the hydatid cysts, 1236 (55.97%) were found to be sterile, 515 (23.32%) were fertile, 323 (14.62%) were calcified, and 174 (7.88%) were observed to have become encrusted (cheesy). Among the local breed, the fertility rate of lung hydatid cysts was higher with 995 (45.06%), followed by the liver with 777 (35.19%), whilst in the imported breed, the fertility rates were 152 (6.88%), and 100 (4.52%) in the lung and liver respectively. This study, observed that Echinococcus granulosus parasite was present in both large and small ruminants within the study area and was responsible for high rate of organ condemnation. Hence, strategic endo-parasite eradication with a strong surveillance system and good management practice of animals is needed in order to limit the impact of the disease among food animals and prevent human transmission.